Using the critical process targeting method to improve SMEs' process understanding: A tale of two Australian case studies. Issue 2 (3rd April 2017) - de Salas, Kristy; Lewis, Ian J.; Huxley, Craig
Abstract : Purpose: Small- and medium-sized enterprises (SMEs) exhibit limited understanding of their business processes. This lack of understanding limits the potential of these businesses and is a direct contributor to the high failure rates of this sector of the economy. Research has suggested that existing BP methods to not support SMEs in gaining an improved understanding of their processes due to the high complexity and resource intensity of these tools, more suitable for deployment within a large business context. The paper aims to discuss these issues. Design/methodology/approach: This paper reports on two qualitative case studies of medium-sized financial entities that employ a new approach, the critical process targeting method (CPTM), to improve their understanding of their processes. Findings: In reviewing these two case studies, the authors find that the CPTM can be considered a useful tool in improving process understanding in SMEs, and can lead to the achievement of strategic goals. This paper, however, also describes a number of practical limitations that were encountered when employing the CPTM within the SME context. Originality/value: This new contribution to theory adds significant and critical support to academia and practice in business process understanding where current methods are found to be too resource heavy for even some large organisations. These two case studies have also provided support for struggling management teams being overwhelmed by the need to understand business processes within their organisations. Published literature and the case study experience both suggest that medium-sized entities have difficulty understanding their business processes.